Geographical Proximity as a Factor of Growth in Sub-Regions of Big Cities in Poland - Gaczek, Wanda Maria (Studia Oeconomica Posnaniensia, 2015)
The article explains the impact of the geographical proximity of enterprises with regard to their functional structure and the influence of the saturation of the gross value of fixed assets and investment in the spatial differentiation of economic growth. It illustrates that geographical proximity provides the possibility of using the traditional benefits of agglomeration and facilitates the flow of knowledge and implementation of innovation. The verification of the six hypotheses was carried out on the basis of a correlation and regression analysis. The main conclusions of the analysis confirm that geographical proximity weighted saturation of selected factors in relation to the number of inhabitants is always a significant factor in creation of the added value of the big city. Big cities in sub-regions maintain a clear and growing competitive advantage over peripheral areas of the country.